Cortisol, obesity, and the metabolic syndrome: A cross‐sectional study of obese subjects and review of the literature12. (12th March 2013) - Abraham, S.B.; Rubino, D.; Sinaii, N.; Ramsey, S.; Nieman, L.K.
Abstract Objective: Circulating cortisol and psychosocial stress may contribute to the pathogenesis of obesity and metabolic syndrome (MS). To evaluate these relationships, a cross‐sectional study of 369 overweight and obese subjects and 60 healthy volunteers was performed and reviewed the previous literature. Design and Methods: Overweight and obese subjects had at least two other features of Cushing's syndrome. They underwent measurements representing cortisol dynamics (24 h urine cortisol excretion (UFC), bedtime salivary cortisol, 1 mg dexamethasone suppression test) and metabolic parameters (BMI, blood pressure (BP); fasting serum triglycerides, HDL, insulin, and glucose). Subjects also completed the Perceived Stress Scale (PSS). UFC, salivary cortisol, and weight from 60 healthy volunteers were analyzed. Results: No subject had Cushing's syndrome. UFC and dexamethasone responses were not associated with BMI or weight. However, salivary cortisol showed a trend to increase as BMI increased (P < 0.0001), and correlated with waist circumference (WC) in men (rs = 0.28, P = 0.02) and systolic BP in women (rs = 0.24, P = 0.0008). Post‐dexamethasone cortisol levels were weak to moderately correlated with fasting insulin (rs = −0.31, P = 0.01) and HOMA‐IR (rs = −0.31, P = 0.01) in men and systolic (rs = 0.18, P = 0.02) and diastolic BP (rs = 0.20, P = 0.009) in women. PSS results were higher in obese subjects than controls, but were not associated with cortisol or metabolic parameters. As expected, WC correlated with fasting insulin, HOMA‐IR, and systolic BP (adjusted for BMI and gender; P < 0.01). Literature showed inconsistent relationships between cortisol and metabolic parameters. Conclusion: Taken together, these data do not support a strong relationship between systemic cortisol or stress and obesity or MS.